”…at undersøge disse Rygters rette Grund førend de sætte Lid til vedkommende Rygtesmeds Fabrikater…”: Løgnagtighed og rygtestorme i et mediehistorisk perspektiv - Lehrmann, Ulrik (K&K - Kultur og Klasse, 2020)
On the basis of the information panic about the Slave War of 1848 in Denmark and the professional ethics and discourse of modern journalism for the printed press of the late 19th century, the question of rumours, untruthfulness and related phenomena in media communication is investigated in a media history perspective. The information panic of 1848 exhibits common features as ’going viral’ within digital media culture. Print news reporting, along with the ethics and discourse of 19th century journalism, served as a means of containing and regulating the flow of information, which is set free again, however, with the emergence of digital media culture. On the basis of this example, I argue in favour of downscaling the status of print media culture as the norm for judging contemporary media culture, including phenomena like ‘fake news’.